Lattice thermal transport in two-dimensional alloys and fractal heterostructures - Aravind Krishnamoorthy (Nature Portfolio, 2021)
Abstract Engineering thermal transport in two dimensional materials, alloys and heterostructures is critical for the design of next-generation flexible optoelectronic and energy harvesting devices. Direct experimental characterization of lattice thermal conductivity in these ultra-thin systems is challenging and the impact of dopant atoms and hetero-phase interfaces, introduced unintentionally during synthesis or as part of deliberate material design, on thermal transport properties is not understood. Here, we use non-equilibrium molecular dynamics simulations to calculate lattice thermal conductivity of $${(Mo|W)Se_2}$$ ( Mo | W ) Se 2 monolayer crystals including $${Mo}_{1-x}{W}_x{Se_2}$$ Mo 1 - x W x Se 2 alloys with substitutional point defects, periodic $${MoSe_2|WSe_2}$$ MoSe 2 | WSe 2 heterostructures with characteristic length scales and scale-free fractal $${MoSe_2}|{WSe_2}$$ MoSe 2 | WSe 2 heterostructures. Each of these features has a distinct effect on phonon propagation in the crystal, which can be used to design fractal and periodic alloy structures with highly tunable thermal conductivities. This control over lattice thermal conductivity will enable applications ranging from thermal barriers to thermoelectrics.